Experimental and numerical investigations on the thermal performance of hemp such a bio-sourced insulation material: application to a Moroccan Mediterranean climate - Dlimi, Maryam; Iken, Omar; Agounoun, Rachid; Zoubir, Amine; Sbai, Khalid (International Journal of Engineering and Technology, 2018)
Thermal performance of hemp concrete and hemp wool such as ecological insulation was evaluated for the city of Meknes in Morocco, in comparison with polystyrene which is an organic insulation material. The study was done in three sections. First, a thermo-physical properties characterization was done using the EI700 device. Then, the study was done on a concrete wall subjected to periodic outdoor conditions. The three insulation materials are used and the effects of thickness, location and partitioning on the time lag and decrement factor were investigated. Finally, heating and cooling loads of a whole building with the use of six different walls configurations are calculated using TRNSYS software. Throughout the whole study, results show that hemp wool presented the best thermal performance, and the evaluation of its use such us an insulation material in Morocco and especially in Meknes was investigated.